Pengaruh Pemberian Ekstrak Daun Terbangun (Coleus Ambonicus Lour) Terhadap Pengeluaran Asi Hari Ke-3 Pada Ibu Primipara Di Rsud Dr.H. Abdul Moeloek Povinsi Lampung - Akrin, Serliana; Yantina, Yuli; Susilawati, Susilawati (MIDWIFERY JOURNAL, 2024)
Introduction The smoothness of breast milk production is influenced by many factors, in some mothers breastfeeding may occur during pregnancy and some occur after delivery, this breastfeeding can affect exclusive breastfeeding for babies where in 2018 the achievement of exclusive breastfeeding in the city of Bandar Lampung was only 69.53 %. One of the efforts to facilitate breastfeeding could be done by giving torbangun leaf extract. The research objective was to know the effect of giving torbangun leaves (coleus ambonicus lour) on the 3rd day of breastfeeding for primiparous mothers at Dr.H Abdul Moloek Regional Public Hospital, Lampung Province.Method This type of quantitative research with a Quasi Experiment research design posttest control group design. The population of all primiparous postpartum mothers on the first day at RSUD Dr.H. Abdul Moeloek Regional Public Hospital, Lampung Province as many as 61 patients, with a sample of 30 people divided into 2 groups, purposive sampling technique sampling. Univariate and bivariate data analysis t-test (t-test).Results showed that the average time to release breastmilk on the 3rd day of postpartum mothers who were given terbangun leaf extract (coleus ambonicus lour) at Dr.H. Abdul Moeloek Regional Public Hospital, Lampung Province for 41.8 hours and Post Partum mothers who were not given terbangun leaf extract (coleus ambonicus lour) for 58.4 hours. There was an effect of giving Terbangun leaf extract (coleus ambonicus lour) on the time of delivery of breast milk on the 3rd day of postpartum primiparous mothers in Dr.H. Abdul Moeloek Regional Public Hospital, Lampung Province  p-value = 0.002 (p-value> α = 0.05). Suggestions for postpartum mothers are expected to consume Terbangun leaves which are made into extracts, or used as dishes such as vegetable soup so that milk production can be accelerated and increased. Keywords : breastmilk production, terbangun leaves extract, primiparous ABSTRAK Latar Belakang Kelancaran produksi ASI dipengaruhi oleh banyak factor, Pada sebagian ibu pengeluaran ASI bisa terjadi dari masa kehamilan dan sebagian terjadi setelah persalinan, pengeluaran ASI ini bisa mempengaruhi pemberian Asi ekkslusif pada bayi dimana di tahun 2018 pencapaian ASI eksklusif di Kota bandar Lampung hanya sebesar 69,53%. salah satu upaya untuk melancarkan ASI dapat silakukan dengan pemberian ekstrak daun torbangun. tujuan  penelitian diketahui pengaruh pemberian daun torbangun (coleus ambonicus lour) terhadap waktu  pengeluaran  asi hari ke-3 pada ibu primipara di RSUD Dr.H Abdul Moloek  Povinsi Lampung Metode Jenis penelitian kuantitatif dengan rancangan penelitian Quasi Eksperimen posttest control group design. Populasi seluruh ibu postpartum primipara hari pertama di  RSUD Dr.H. Abdul Moeloek Povinsi Lampung sebanyak 61 pasien, Dengan  sampel sebanyak 30 orang yang di bagi menjadi 2 kelompok, teknik sampling purposive sampling. Analisa data univariat dan bivariat uji t (t-test).Hasil Diketahui rata-rata waktu  pengeluaran ASI hari ke-3 pada ibu Post Partum yang diberi ekstrak daun torbangun (coleus ambonicus lour) di RSUD Dr.H. Abdul Moeloek  Povinsi Lampung  selama 41,8 jam dan ibu Post Partum yang tidak diberi ekstrak daun torbangun (coleus ambonicus lour) selama 58,4 jam. Ada Pengaruh  pemberian ekstrak Daun Torbangun (coleus ambonicus lour) terhadap waktu  pengeluaran ASI hari ke-3 ibu Post Partum primipara di RSUD Dr.H Abdul Moeloek  Povinsi Lampung  p-value = 0, 002 (p-value > α = 0,05). saran bagi Ibu nifas di harapkan dapat mengkonsumsi daun torbangun yang di jadikan ekstrak, atau dijadikan masakan seperti sayur sop sehingga produksi ASI dapat dipercepat dan semakin meningkat.Kata kunci: penegeluaran ASI, ekstrak daun torbangun, primipara